Predictors of desire to limit childbearing among reproductive age women in high fertility regions in Ethiopia. A multilevel mixed effect analysis - Wubshet Debebe Negash; Tadele Biresaw Belachew; Desale Bihonegn Asmamaw; Desalegn Anmut Bitew (BMC, 2023)
Abstract Background A high fertility rate can have a number of expensive consequences for developing nations, such as limiting economic growth, adversely impacting women and their children's health, and reducing access to quality education, nutrition, and employment. The problem is more obvious in Ethipia's high fertility regions. Therefore, this study aimed to assess predictors of desire to limit childbearing among reproductive age women in high fertility regions in Ethiopia. Methods The analysis was based on secondary data using the 2016 Ethiopian Demographic and Health Survey. Stata version 14 software was used for analysis. A multi-level mixed-effect logistic regression analysis was fitted. Adjusted Odds Ratio at 95% confidence interval was used to show the strength and direction of the association. Statistical significance was declared at a P- value less than 0.05. Results The overall desire to limit childbearing in high fertility regions in Ethiopia was 37.7% (95% CI: 36.28, 39.17). Age; 25-34 (AOR = 3.74; 95% CI: 2.97, 4.73), 35-49 years (AOR = 14; 95% CI: 10.85, 18.06), women education; Primary education (AOR = 0.73; 95% CI: 0.61, 0.88), secondary and higher (AOR = 0.29; 95% CI: 0.19, 0.43), from the community level variables Oromia National Regional state (AOR = 5.86; 95% CI: 2.82, 12.23), high proportion of community level poverity (AOR = 0.67; 95% CI: 0.45, 0.98), and high proportion of community level media exposure (AOR = 1.53; 95% CI: 1.07, 2.19) were statistically significant factors for desire to limit childbearing in high fertility regions of Ethiopia. Conclusion Nearly four in ten women had the desire to limit childbearing in high fertility regions in Ethiopia. Thus, to fulfill the women's desire to limit childbearing, Ministry of Health and health facilities are needed to increase financial support strategies and Family planning programs that enable pregnant women from poor households to use health services. In addition, increasing community level media exposure are important interventions.